Extending ecological niche models to the past 120 000 years corroborates the lack of strong phylogeographic structure in the Crested Drongo (Dicrurus forficatus forficatus) on Madagascar. (6th February 2013) - Fuchs, Jérôme; Parra, Juan L.; Goodman, Steven M.; Raherilalao, Marie Jeanne; Vanderwal, Jeremy; Bowie, Rauri C. K.
<x xml:space="preserve">Abstract</x> We conduct a phylogeographic study of the Crested Drongo (Dicrurus forficatus forficatus), a broadly distributed bird species on Madagascar. We first determined the demographic and spatial pattern inferred from mitochondrial and nuclear data, and then compared these results with predictions from a present to 0.120‐Myr‐old reconstruction of the spatial dynamics of the range of D. f. forficatus on Madagascar, enabling putative areas of stability (lineage persistence) to be detected. Weak genetic structure along an east–west pattern and comparatively low genetic diversity were recovered, with strong evidence of population expansion found at all ten loci sampled. The palaeoclimatic distribution models over the past 0.120 Myr suggest the presence of extensive areas of suitable climate in the east and west for the species since its colonization of Madagascar, a result in strong concordance with the spatial and genetic signal derived from our multilocus data set. © 2013 The Linnean Society of London